Expertreview Modul Produktivitas Ikan Mas untuk Pembelajaran Kimia di Era New Normal - K. Anom W; Dian Novriana; Eka Ad'hiya; Maefa Eka Haryani (Orbital: Jurnal Pendidikan Kimia, 2022)
Modules for entrepreneurship courses are still very few topics, so they still need to be developed. The topic of goldfish feed is an important topic for the module to develop, due to the high consumption of goldfish in the community, which can be a business opportunity. This study aims to describe development of validation instrumen for Expert Review of development for chemistry learning modules based on STEM (science, technology, engineering, and mathematics) that are appropriate according to development research experts. This type of research uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) which is combined with the Tessmer Evaluation. This research method is descriptive qualitative, interview, observation, and documentation. The object of this research is the Development of Validation Instruments for STEM-Based Chemistry Learning Modules for Entrepreneurship Courses in the New Normal era at Sriwijaya University Chemistry Education, Topic of Feed to Increase goldfish Productivity. The development was carried out by an Expert Review in the form of consultation with development research experts to obtain appropriate Content Validity, Pedagogy and Practicality Instruments according to experts. The results of expert review were then analyzed by calculating the item validity index. Based on the final results of this study, it was found that the Content Validity, Pedagogy, and Practicality Instruments were qualitatively suitable for use in STEM-based chemistry learning modules on feed topics to increase Goldfish Productivity in the New Normal era.